The shadow of paternalism on patient-centeredness in oncology nursing care: A barrier of health-care promotion - Fariba Taleghani; Saba Farzi; Ahmadreza Yazdannik; Mehran Sharifi Esfahani (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Patient-centered care (PCC) is a key component of high-quality care. Given the different effects of cancer on patients, patient-centeredness is very important in oncology nursing care. The aim of this study was to explore nurses' perceptions of the patient-centered in oncology nursing care. MATERIALS AND METHODS: This descriptive qualitative study was conducted in 2018-2020, Iran. Data collection methods included observation and semi-structured interviews. Patient, family, and nurse behaviors were observed (total: 318 h). In addition, interviews were conducted with nurses and nursing managers (12 interviews). Data analysis was performed using Graneheim and Lundman's approach. RESULTS: Data analysis resulted in the emergence of four themes: "Organizational structure as a barrier to the PCC," "Lack of institutionalization of PCC in nurses," "Understanding and paying attention to the patient as PCC," and "Situational PCC." The final theme of this study is "PCC in the shadow of paternalism." CONCLUSIONS: The paternalism approach in the context of oncology nursing care has made the realization of PCC difficult. The first step to promote PCC is increasing nurses' awareness of the impact of paternalism on patient-centeredness. Providing patient-centered oncology nursing care requires changing attitudes, values, and behaviors at individual, professional, and organizational levels.